Campylobacteriosis in An Outbreak of Foodborne Disease at Bantar Gadung Village Palabuhan Ratu - Luhung Budiailmiawan; Ida Parwati; Coriejati Rita; Dewi Lokida (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Campylobacteriosis is a rare enteritis case in Indonesia. On September 12, 2019, there was an outbreak of foodborne diseases with the symptoms of fever, abdominal cramps, and bloody diarrhea after eating food from the Tahlilan (funeral prayer) ceremonial at Bantar Gadung village Palabuhan Ratu Sukabumi. The laboratory and epidemiological investigationwere performed. Fresh stool samples were collected from 18 suspected cases. Gram stain, routine stool examination, and PCR were performed. The PCR method was used based on the nested PCR method by Platts-Mills et al. for Campylobacter spp. The positive result was identified by visualization in gel electrophoresis at 816-bp. Interview, environmental investigation, and analysis of incidence rate were performed for epidemiological study. The majority of patients were males aged 33-48 years old. The main symptoms were fever (100%), abdominal cramps (100%), and bloody diarrhea (11/18;61%). Nine of them (9/11; 82%) were confirmed by Gram staining as Gram- negative bacteria, with comma, s-shaped, or seagull appearance, as presumptive Campylobacter spp. Two patients (2/18;11%) were confirmed infected with Campylobacterspp. by PCR and sequencing tests. It has been found that this outbreak was caused by food contaminated with Campylobacter spp. The incidence rate of Campylobacteriosis in this outbreak was 11%.